Re-Intermediation, Audience Development and the Discourse of the European Film Public: Festival Scope and Curzon Home Cinema (Cinéma & Cie. Film and Media Studies Journal, 2017)
This article considers two recent attempts at developing networked lm cultures in online exhibition spaces. Focusing on two video-on-demand platforms, Festival Scope and Curzon Home Cinema, the article examines how VOD is being positioned and utilized as a tool to develop lm-literate audiences while also serving the interests of the lm industry by promoting and exposing lms to different geographic markets. While Festival Scope originated as a platform for industry insiders to view and gather information about lms, Curzon Home Cinema has emerged in the last ve years as a leader in day-and-date online releases of art lms for audiences in the UK and Ireland. The emergence and growth of both platforms is examined with special attention to the rhetoric of on-demand spectatorship as a special event. In both cases, the platforms’ presentation of lms on-demand, concurrent with their theatrical (Curzon) or festival (Festival Scope) screenings, is offered to audiences as a privileged moment of participation in lm culture. The article then argues that these platforms should be understood in close relation to the prevalent discourses of European lm policy, funding and industrial support. Both Festival Scope and Curzon are funded in part by Creative Europe’s Media programme. The article situates the growth of these on-demand platforms in relation to Creative Europe’s competing cultural and economic discourses of public access and competitiveness. An analysis of Creative Europe’s funding schemes reveals how VOD gures into the goals of European cultural and economic integration. The re-intermediation of lm culture that is fostered by VOD platforms such as Festival Scope and Curzon is considered with regards to how it aligns with Creative Europe’s cultural and economic objectives and its emphasis on digitalization and transnationalism.